Haematopoietic stem cell transplantation as first-line treatment in myeloma: a global perspective of current concepts and future possibilities - Catriona Elizabeth Mactier; Md Serajul Islam (Frontiers Media S.A., 2012)
Stem cell transplantation forms an integral part of the treatment for multiple myeloma. This paper reviews the current role of transplantation and the progress that has been made in order to optimize the success of this therapy. Effective induction chemotherapy is important and a combination regimen incorporating the novel agent bortezomib is now favorable. Adequate induction is a crucial adjunct to stem cell transplantation and in some cases may potentially postpone the need for transplant. Different conditioning agents prior to transplantation have been explored: high-dose melphalan is most commonly used and bortezomib is a promising additional agent. There is no well-defined superior transplantation protocol but single or tandem autologous stem cell transplantations are those most commonly used, with allogeneic transplantation only used in clinical trials. The appropriate timing of transplantation in the treatment plan is a matter of debate. Consolidation and maintenance chemotherapies, particularly thalidomide and bortezomib, aim to improve and prolong disease response to transplantation and delay recurrence. Prognostic factors for the outcome of stem cell transplant in myeloma have been highlighted. Despite good responses to chemotherapy and transplantation, the problem of disease recurrence persists. Thus, there is still much room for improvement. Treatments which harness the graft-versus-myeloma effect may offer a potential cure for this disease. Trials of novel agents are underway, including targeted therapies for specific antigens such as vaccines and monoclonal antibodies.